Small Scale Electricity Generation from a Portable Biomass Cookstove: Prototype Design and Preliminary Results - O'Shaughnessy, Seamus; Robinson, Anthony (My University, 2013)
The World Health Organisation estimates that over 20% of the global population (~1.4 billion people) lack access to electricity. Furthermore, 40% of the global population (~2.7 billion people) rely on the traditional use of biomass for cooking (WHO 2011, OEDC/IEA, 2010). This study details the development of aprototype electrical generator for portable stoves commonly in use in the developing world. This generator is capable of delivering small amounts of off-grid electricity. Power is generated using the thermoelectric effect. A single thermoelectric module is utilised to convert asmall portion of heat from the stove to electricity. The electricity produced is used to charge a single 3.3 V lithium?iron phosphate battery and drive a low power fan, as well as some other auxiliary features. The airflow produced by the fan is used in conjunction with a commercially available heat pipe heat sink to maintain an adequate temperature difference across the thermoelectric module. From experiments in the laboratory, a maximum TEG power output of 5.9 W has been obtained. On average, 3 W h of energy was stored in a battery during a typical 1 h long burn. Three 1 h long burns produced sufficient energy to fully charge the battery. The performance of the electricity generating cooking stove has subsequently been tested in Malawi using locally sourced fuel and fire stoking methods.
PUBLISHED
Keywords: Biomass; Cookstove; Thermoelectric; Electricitygeneration; Lighting; Phone charging; Biomass; Cookstove; Thermoelectric; Electricitygeneration; Lighting; Phone charging; International Development; Smart & Sustainable Planet; Telecommunications